(untitled) (Tanzania Medical Journal, 2022)
Introduction The Medical and Dental Council of Nigeria (MDCN) and the National Universities Commission (NUC) designed the medical undergraduate curriculum with one of its core objectives being “To produce medical and dental practitioners with sufficient managerial ability to play a leadership role in health care delivery”. The extent to which this is implemented in Nigeria medical schools is yet to be explored. The aim of this study was to assess whether leadership and management courses were taught to students during their studies Methods Eighty-three medical students in their 5th and 6th year in 3 randomly selected medical schools in Nigeria responded to an online self-administered questionnaire from February 20, 2020 to March 2, 2020. Information on whether any formal leadership and management courses were taught in their syllabus was sought, and they also answered questions on how well instructors taught their general courses. Application of perceived knowledge of leadership using 4Cs (communication, critical thinking, collaboration and creativity) in 21st century learning was assessed using hypothetical leadership case scenario. Results Sixty-nine of the 83 respondents (83.1%) did not have leadership and management training in their study years, p = 0.001 and (74.7%) did not have faculty mentors. Few respondents (31.65%) thought their instructors were generally well organized, and thirty-three (40.74%) of respondents thought their instructors answered their questions above average. Many responders ticked the correct answers to the labels of 4 Cs of 21st century learning but application of this knowledge to a hypothetical leadership scenario was poor as only 7 respondents gave some plausible solutions to the problem. Conclusion Most medical students lack formal leadership training in Nigeria and these skills are needed in their early career to manage clinics and hospitals in rural and some urban settings. The implication is that should these doctors be sent to these clinics, they may fail to lead them properly, so training modules should be integrated into the already packed curriculum from the first year through the final year of study to improve the leadership of clinics.